Teachers' construction of their roles and responsibilities for inclusive language practices with multilingual parents - a case from Norway - Thyness, Hilde (Language and education, 2024)
While Norwegian educational policy documents construct an overarching role for the teacher as the main party responsible for inclusion in the parent-school cooperation, there are conflicts in the associated discourses on language and inclusion. This can lead to uncertainties in terms of the teachers' responsibilities for inclusion in the parent-teacher interaction. This paper considers some of the constraints and ambivalences experienced by teachers in multilingual contexts, and more precisely investigates the subject positions made available through political and societal discourses and locally emerging teacher discourses. Examining parent-teacher interaction in both online and offline contexts, the study is guided by the following research question: How do Norwegian teachers construct their roles and responsibilities for inclusive language practices with parents who have Norwegian as an additional language? The analysis shows that the teachers' values concerning inclusive practices open up for an asset-orientation towards multilingualism. However, the potentials of these discourses of ideals are curbed by monolingual ideologies due to the lack of awareness, and of material, institutional and relational support. These constraints seem to be more prominent in the digitally mediated interaction than in face-to-face meetings, which deserves our attention as we know that parent-school interaction increasingly takes place via digital channels.